Grouping of Regencies/Cities In West Sumatra Province Based On Economic Development Indicators Using The Self-Organizing Maps (SOM) Algorithm - Wiwil Dzil Izzatil; Chairina Wirdiastuti; Syafriandi (Universitas Islam Negeri Alauddin Makassar, 2025)
Economic development is an important aspect in improving the standard of living of the community. To measure economic development progress in a region, relevant indicators are needed, one of which is Gross Regional Domestic Product (GRDP) per capita. In West Sumatra Province, there are disparities in RDP per capita between regions. Therefore, clustering is necessary to assist local governments in determining development priorities, formulating more targeted development policies, and allocating resources efficiently. This study aims to cluster West Sumatra regions using the Self-Organizing Maps algorithm based on economic development indicators. The analysis results identified three clusters: Cluster 1 consists of 6 districts/cities categorized as having moderate economic development, Cluster 2 includes 7 districts/cities with high economic development, and Cluster 3 consists of 6 other districts/cities categorized as having low economic development.